Comparison of different technologies for producing recombinant adeno-associated virus on a laboratory scale - E. I. Ryabova; A. A. Derkaev; I. B. Esmagambetov; D. V. Shcheblyakov; M. A. Dovgiy; D. V. Byrikhina; V. V. Prokofiev; I. P. Chemodanova (Биопрепараты: Профилактика, диагностика, лечение, 2021)
Adeno-associated virus vectors are among the most promising ones for the delivery of transgenes to various organs and tissues. Recombinant adeno-associated virus (rAAV) is able to transduce both dividing and non-dividing cells, has low immunogenicity, and is able to provide long-term expression of transgenes. Modern technologies make it possible to obtain rAAV for in vivo use, but they are not without drawbacks associated with laboriousness, scalability difficulties, and high cost, therefore, improvement of technological schemes for obtaining rAAV is an urgent issue. The aim of the study was to compare different technological approaches to rAAV production based on different conditions of the transfected HEK293 cell line cultivation on a laboratory scale. Materials and methods: HEK293 cell culture, AAV-DJ Packaging System, PlasmidSelect Xtra Starter Kit were used in the study. The technologies were compared using a model rAAV vector with a single-domain antibody transgene fused to the Fc-fragment of IgG1 specific to botulinum toxin. HEK293 cells were transfected with supercoiled plasmid DNA isolated by three-step chromatographic purification. The identity of the rAAV preparation was determined by electrophoresis, immunoblotting, and real-time polymerase chain reaction. Results: the study demonstrated the efficiency of the chromatographic method for obtaining a supercoiled form of plasmid DNA that can be used for efficient transfection of cell culture in order to produce rAAV. The study compared the following processes of rAAV production: using transient transfection and cultivation of the transfected HEK293 cell suspension in Erlenmeyer flasks, adherent culture in T-flasks, and adherent culture in a BioBLU 5p bioreactor on a matrix of Fibra-Cel disks. Conclusions: the data obtained showed the possibility of using the described approaches to purification of plasmid DNA, cell transfection, and cultivation of the transfected cells under various conditions to obtain rAAV samples that expresses the antibody gene. The BioBLU 5p reactor with Fibra-Cel discs was used for the first time to produce preparative quantities of rAAV on a laboratory scale, which increased the adherent surface area during cell culture and transfection, and, as a result, increased the yield of the target product.